Revealing The Criterion On Botnets Detection Technique - Abdullah, Raihana Syahirah; Abdollah, Mohd Faizal; Muhamad Noh, Zul Azri; Mas'ud, Mohd Zaki; Selamat, Siti Rahayu; Yusof, Robiah (IJCSI, 2013)
-